Pengaruh Media Pembelajaran Flashcard Terhadap Kemampuan Menulis Aksara Sunda Siswa Sekolah Menengah Atas - Cahya Somantri; Opah Ropiah (Jurnal Studi Guru dan Pembelajaran, 2025)
The purpose of this study is: 1) to describe the results of students before using flashcard learning media on the ability to write Sundanese script in SMA Negeri 1 Bantarujeg class X; 2) to describe the results of students after using flashcard learning media on the ability to write Sundanese script in SMA Negeri 1 Bantarujeg class X; 3) to describe the effect of flashcard learning media on the ability to write Sundanese script in SMA Negeri 1 Bantarujeg class X. The method used in this study is an experimental research method with a One-Group Pretest Posttest Design design with a quantitative research approach. The sampling technique used in this study is using purposive sampling, the sample is class X.2 students of SMA Negeri 1 Bantarujeg, Majalengka Regency. Data collection techniques through observation, testing and documentation. The instrument used was a pretest-posttest question. The data analysis techniques used in this study were validity testing, normality testing, and hypothesis testing. The results of the study were that before using flashcard learning media on the ability to write Sundanese script, the largest pretest value was 80 while the smallest value was 10 with an average of 39.43. After applying flashcard learning media to the ability to write Sundanese script, the largest posttest value was 90 while the smallest value was 50 with an average of 73.86. From the test results, the Sig. (2-tailed) value is 0.000. This means that Sig. (2 tailed) <0.005. It can be concluded that there is a difference in the average value of students before and after using flashcard learning media on the ability to write Sundanese script. Thus, flashcard learning media has a significant influence on the ability to write Sundanese script in SMA Negeri 1 Bantarujeg Class X.